Sequential Entry in a Vertically Differentiated Duopoly - Luca Lambertini; Piero Tedeschi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We analyse a model of vertical differentiation focusing on the trade-off between entering early and exploiting monopoly power with a low quality, versus waiting and enjoying a dominant market position with a superior product. We show that there exists a unique equilibrium where the leader enters with a lower quality than the follower, for low discount factors, for high costs of quality and for low consumers' willingness to pay for quality.
Keywords: 330